The Demographic Variables and Their Impact on Job Satisfaction of Bank Employees - Aloysius, S.M.C.M. (JUICE- 2012 University of Jaffna, 2012)
The study investigated the influence of demographic variables on job satisfaction of the bank employees. Job satisfaction is one of the major determinants of the physical, psychological and the social wellbeing of an employee. The main objective of the study was to find out the gender differences in the level of satisfaction where the work environment perceived as male dominated. For the purpose of this study 62 employees have been selected from private banks in Jaffna district, using simple random sampling. A self administrated questionnaire issued them with 5 point Likert scale which consists of three parts. Two hypotheses were formulated and tested in the study. Even though 84% of female reported the work environment is male dominated, the level of job satisfaction is higher than their male counterparts (80% whereas the male 72%). The analysis proved there is no major difference caused in job satisfaction due to the demographic variables other than sex.
Keywords: Demographic variables; Job satisfaction; Male domination